Bistable Nonlinear Energy Sink Using Magnets and Linear Springs: Application to Structural Seismic Control - Y. Y. Chen; W. Zhao; C. Y. Shen; Z. C. Qian (Shock and Vibration)
Nonlinear energy sink (NES) has proven to be very effective in reducing the vibration response of structures. In this paper, a magnetic bistable nonlinear energy sink (BNES) that composed of a guided moving mass attached with linear springs and permanent magnets is proposed. To assess the seismic control performance of the proposed BNES, a shear frame model equipped with the proposed BNES is compared with the same shear frame model equipped with an optimized cubic NES and with a linear tuned mass damper (TMD) system. The results show that, in the idealized situation, where the mass and stiffness is clearly defined (no uncertainty), the BNES can achieve similar performance as a thoroughly in-tuned TMD system. Moreover, in the detuned condition, due to broadband high internal resonance capability, the proposed BNES can outperform the linear TMD and the cubic NES. The study demonstrates that the proposed BNES can be used as an efficient passive vibration absorber for structural seismic control.